UPAYA MENINGKATKAN MOTIVASI DAN KINERJA KARYAWAN DALAM PENERAPAN SISTEM SHIFT KERJA PADA PT ANGKASA PURA 1 - Adi Purnama; I Made Chandra Mandira; Ni Wayan Merry Nirmala Yani; Kadek Linda Kusnita; I Wayan Aditya Tariana; Gede Crisna Wijaya (Cv. Utility Project Solution, 2023)
The importance of human resources in a company shows that companies must be able to manage and empower the human resources they have Empowering human resources in a company can be done in various ways. Some ways that can be done are to improve the performance of an employee through increasing the discipline and motivation efforts of employees. (Mangkunegara Anwar Prabu, 2009). PT Angkasa Pura I is one of the largest companies in Indonesia. The author himself is currently implementing a PKL program in this institution. The problem that the author sees happening is the lack of discipline and motivation of employees which has an impact on their performance in the company. The results to be achieved were not optimal. So inevitably there must be more improvements to evaluate the performance that has not been achieved by this agency. The purpose of this community service is to find out what efforts should be made by PT. Angkasa Pura I in increasing employee motivation and performance through the implementation of a work shift system. Improving performance can be done in various ways, one of which is by applying work discipline. Because from what the author sees, work discipline at PT Angkasa Pura is still not optimal and because of the lack of work discipline, the performance of employees is still less productive even though it should be improved again.